Policy evaluation of place-based strategies on upgrading county industrial structures amid economic structural transformation: Insights from pilot counties of China's returning entrepreneurs. - Xianghui Tian; Zhang Juan (PLoS ONE)
In the context of the transformation of urban-rural dual economic structure, one of the important ways to realize urban-rural integrated development is to carry out county industrial structure upgrading. Based on the policy of returning home to start business as a quasi-natural experiment, this paper empirically analyzes the relationship between returning home to start business and upgrading of county industrial structure. Selecting 1997 counties across the country from 2000 to 2021 as the research sample, a multi-temporal double-difference model is used to test the impact of the place-based policy on county industrial structure and the mechanism of the impact, and the result confirms that the implementation of the pilot policy of returning home entrepreneurship plays a positive and obvious role in promoting the level of industrial development of county-level areas. Subsequent investigations reveal diverse regional impacts, notably in Central and Western and the significantly older regions; thus, the influence of the prototype program of reintroducing home entrepreneurship on enhancing industrial development is more pronounced. Viewing from a mechanistic standpoint, the pilot initiative, which motivates entrepreneurs to go back and establish new businesses, aids in enhancing industrial frameworks by boosting innovation and stimulating the market. The article offers valuable direction and understanding to decision-makers aiming to enhance the combined growth of urban and rural sectors, as well as to elevate and reform the economy.